Reduced primary care respiratory infection visits following pregnancy and infancy vitamin D supplementation: a randomised controlled trial. (21st October 2014) - Grant, Cameron C.; Kaur, Suhina; Waymouth, Ellen; Mitchell, Edwin A.; Scragg, Robert; Ekeroma, Alec; Stewart, Alistair; Crane, Julian; Trenholme, Adrian; Camargo, Carlos A.
Abstract: Aim: To determine whether vitamin D supplementation reduces primary care visits for acute respiratory infection (ARI). Methods: A randomised, double‐blind, placebo‐controlled trial was conducted in New Zealand and powered to determine the vitamin D dose needed to achieve normal vitamin D status during infancy. Healthy pregnant women, from 27 weeks' gestation to birth, and their infants, from birth to age 6 months, were assigned to placebo or one of the two dosages of daily oral vitamin D3 . Woman/infant pairs were randomised to placebo/placebo, 1000 IU/400 IU or 2000 IU/800 IU. For this ad hoc analysis, the primary care records of enrolled children were audited to age 18 months. Results: Two hundred and sixty pregnant women were randomised to placebo (n = 87), lower‐dose (n = 87) or higher‐dose (n = 86) vitamin D3 . In comparison with the placebo group (99%), the proportion of children making any ARI visits was smaller in the higher‐dose (87%, p   =   0.004), but not the lower‐dose vitamin D3 group (95%, p   =   0.17). The median number of ARI visits/child was less in the higher‐dose vitamin D3 group from age 6–18 months (placebo 4, lower dose 3, higher dose 2.5; p   =   0.048 for higher‐dose vitamin D3 vs. placebo). Conclusion: Vitamin D3 supplementation during pregnancy and infancy reduces primary care visits for ARI during early childhood. Abstract :